Translation and genetic criticism: Genetic and editorial approaches to the ‘untranslatable’ in Joyce and Beckett - Van Hulle, Dirk (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
A genetics of translation may suggest a unidirectional link between two fields of research (genetic criticism applied to translations), but there are many ways in which translation and genetic criticism interact. This article’s research hypothesis is that an exchange of ideas between translation studies and genetic criticism can be mutually beneficial in more than one way. Their main function is to enhance a form of textual awareness, and to this end they inform each other in at least five different ways: genesis as part of translation; translation of the genesis; genesis of the translation; translation as part of the genesis; and finally the genesis of the untranslatable. To study this nexus translation/genetic criticism the works of James Joyce and Samuel Beckett will serve as case studies.